UV sensing properties of ZnO nanowires/nanorods - Chatchai Rodwihok (2018)
© 2017 Elsevier B.V. This work presents a synthesis of vertically aligned and uniform ZnO nanowires/nanorods (NWs/NRs) for the fabrication of ultraviolet (UV) photodetectors. ZnO was grown on Zn seed layer substrates by chemical vapor deposition (CVD) technique. The glass substrates were seeded with Zn at different deposition temperatures. The experimental results showed that surface morphology consists of mixed ZnO NWs/NRs shapes with preferential growth orientation on the c-axis. The increase of uniformity, diameter, and growth density was strongly dependent on the deposition temperatures of the Zn seed layer. The average diameter of mixed ZnO NWs/NRs increased from 50-350 nm with the increasing of the deposition temperature. The growth density is discussed in terms of the nuclei probability. Moreover, a novel blunt-pin on the top of ZnO NWs/NRs was observed under 450 °C condition due to change of growth rate on the crystal facet. The photoresponse of the UV sensor based on ZnO NWs/NRs was examined using UVA lamp (365 nm). The results showed that a high photo sensitivity with fast response and recovery times can be achieved upon the adsorbed electrons due to ultrahigh surface-to-volume ratio.